Germline predisposition to haematological malignancies: Best practice consensus guidelines from the UK Cancer Genetics Group (UKCGG), CanGene‐CanVar and the NHS England Haematological Oncology Working Group. (6th February 2023) - Speight, Beverley; Hanson, Helen; Turnbull, Clare; Hardy, Steven; Drummond, James; Khorashad, Jamshid; Wragg, Christopher; Page, Paula; Parkin, Nicholas W.; Rio‐Machin, Ana; Fitzgibbon, Jude; Kulasekararaj, Austin Gladston; et al.
Summary: The implementation of whole genome sequencing and large somatic gene panels in haematological malignancies is identifying an increasing number of individuals with either potential or confirmed germline predisposition to haematological malignancy. There are currently no national or international best practice guidelines with respect to management of carriers of such variants or of their at‐risk relatives. To address this gap, the UK Cancer Genetics Group (UKCGG), CanGene‐CanVar and the NHS England Haematological Oncology Working Group held a workshop over two days on 28–29th April 2022, with the aim of establishing consensus guidelines on relevant clinical and laboratory pathways. The workshop focussed on the management of disease‐causing germline variation in the following genes: DDX41, CEBPA, RUNX1, ANKRD26, ETV6, GATA2 . Using a pre‐workshop survey followed by structured discussion and in‐meeting polling, we achieved consensus for UK best practice in several areas. In particular, high consensus was achieved on issues regarding standardised reporting, variant classification, multidisciplinary team working and patient support. The best practice recommendations from this meeting may be applicable to an expanding number of other genes in this setting.